Morbidity scoring after abdominal surgery. (December 2016) - Graf, Rolf; Cinelli, Paolo; Arras, Margarete
Postoperative monitoring of pain and distress in small rodents is not standardized, and widely accepted score sheets are not available. Here we describe a score sheet used in abdominal surgery of rodents, with particular reference to procedures involving the liver.